AI*IA 2005: Advances in Artificial Intelligence 9th Congress of the Italian Association for Artificial Intelligence Milan, Italy, September 21-23, 2005, Proceedings - Manzoni, Sara (Lecture Notes in Artificial Intelligence, 2005)
This volume collects the papers selected for presentation at the IX Congress of the Italian Association for Arti?cial Intelligence (AI*IA), held in Milan at the University of Milano-Bicocca (September 21-23, 2005). On the one hand this congress continues the tradition of AI*IA in organizing its biannual s- enti?c meeting from 1989; on the other hand, this edition is a landmark in the involvement of the international community of arti?cial intelligence (AI), directly involving a broad number of experts from several countries in the P- gramCommittee. Moreover,the peculiar nature of scienti?c researchin arti?cial intelligence (which is intrinsically international) and several consolidated int- national collaborations in projects and mobility programs allowed the collection and selection of papers from many di?erent countries, all around the world, enlarging the visibility of the Italian contribution within this research ?eld. Arti?cial intelligence is today a growing complex set of conceptual, theor- ical, methodological, and technological frameworks, o?ering innovative com- tational solutions in the design and development of computer-based systems. Within this perspective, researchers working in this area must tackle a broad range of knowledge about methods, results, and solutions coming from di?erent classical areas of this discipline. The congress was designed as a forum allowing researchers to present and discuss specialized results as general contributions to AI growth.